Case report: Uncommon presentation of Salmonella Dublin infection as a large paravertebral abscess - An, Kang; Wu, Zengxiang; Zhong, Cejun; Li, Shuangqing (Frontiers in Medicine, 2023)
Background: Salmonella Dublin is a zoonotic pathogen that is associated with invasive infections and high morbidity and mortality rates. Here we present the case of a 78-year-old man with a rare manifestation of a paravertebral abscess in the thoracolumbar spine caused by Salmonella Dublin. Case presentation: The patient had a history of spinal tuberculosis and poorly controlled diabetes. The abscess was successfully managed by drainage, and a 12-week course of moxifloxacin resulted in complete recovery. Salmonella Dublin was identified using culture-based serotyping. The patient resided in an environment where cattle farming is common; he consumed raw beef and unpasteurized milk, suggesting a potential source of infection. Discussion: Increasing the awareness of Salmonella Dublin as a potential cause of spinal abscesses is important, particularly in patients with structural spinal abnormalities. The timely initiation of appropriate antimicrobial therapy based on susceptibility testing is recommended. This case highlights the pathogenic potential of Salmonella Dublin and emphasizes the importance of effectively managing invasive Salmonella infections.